Characterizations of carbon nanotubes grown on clay - S. Aodkeng (2020)
© Published under licence by IOP Publishing Ltd. Carbon nanotubes (CNTs) are nano materials that have unique physical and mechanical properties. Carbon nanotubes grown on clay (Clay-CNTs) are new hybrid material based on clay mineral. Clay minerals were used as catalyst for CNTs synthesis by chemical vapor deposition at 700 °C for 1 hour. In this work, Clay-CNTs were investigated by various analytical techniques such as X-ray diffraction (XRD), scanning electron microscope (SEM) and electron diffraction spectrometer (EDS) and Raman spectroscopy to analyse the phase identification of crystalline, morphology and crystallinity quality of Clay-CNTs. Moreover, thermogravimetric analysis (TG) was studied to ident ify phase deco mposition. XRD results indicate crystallites of the CNTs have (002), (101) and kaolinite and quartz from clay mineral catalyst. SEM images of Clay-CNTs showed cluster of CNTs on carbon fiber and their wormlike morphology. The intensity of Raman spectra of Clay-CNTs reveals the defect of CNTs structure. TGA derivative profile indicated decomposition of CNTs and kaolin.